USE OF PICTURE AND PICTURE MODEL BASED ON MULTIMEDIA WITH INTERNALIZE CHARACTER EDUCATION ON LANGUAGE CIVILIZED - Dewi Afriany Susanti (IKIP Siliwangi, 2018)
The research conducted is Classroom Action Research by using Picture and picture model based on multimedia by internalizing character education on civic education Subject, State IV State Elementary Matter Material 040448 Kabanjahe Lesson Year 2016/2017.The location of this research is SD Negeri 040448 Kabanjahe. The subjects in this study were third-grade students of SD Negeri 048232 Kabanjahe which amounted to 49 students and as an object is an improvement of learning on the material of State Coat by using Picture and picture model based on multimedia.Data Collection Techniques are Observation Sheet Teachers and Observation Sheets of student activities. Data analysis techniques used were observation and test sheets.Based on the research that has been done then the implementation of learning activities of teachers 80% (good category), the implementation of learning activities 87 students (good category), and student learning outcomes 85% classically, and the average value 82.From the results of this study can be concluded that the implementation of learning included into both categories, and student learning outcomes have been increased and completed in a classical manner using the Picture and picture model based on multimedia to Improve Student Results on civic education Subjects, State IV State Elementary School 040448 Kabanjahe Lesson Year 2016/2017.